Feel good now or regret it later? The respective roles of affective attitudes and anticipated affective reactions for explaining health‐promoting and health risk behavioral intentions. Issue 6 (1st March 2019) - Stevens, Courtney J.; Gillman, Arielle S.; Gardiner, Casey K.; Montanaro, Erika A.; Bryan, Angela D.; Conner, Mark
Abstract: Evidence supporting the incorporation of affective constructs, such as affective attitudes and anticipated regret, into theoretical models of health behavior has been mounting in recent years; however, the role of positive anticipated affective reactions (e.g., pride) has been largely unexplored. The purpose of the present investigation was to assess how affective attitudes and anticipated affective reactions (both pride and regret for performing a behavior or not) may provide distinct utility for understanding intentions to perform health‐promoting and health risk behaviors over and above cognitive attitudes and other established theoretical constructs from the theory of planned behavior (TPB). Participants ( N = 210) were recruited via Amazon's Mechanical Turk to complete a one‐time online battery assessing TPB and affective constructs. Self‐reported intentions served as the main outcome measure, and hierarchical linear modeling was used to examine the effects of TPB and affective constructs across behaviors. Controlling for TPB constructs, more positive affective attitudes and greater anticipated regret, but not anticipated pride, predicted intentions to engage in future health behaviors. Anticipated affective reactions contributed explanatory variance for intentions to perform health risk behaviors, but anticipated pride and regret were not associated with intentions to perform health risk behaviors. Contributions made via the inclusion of both positively and negatively valence anticipated affective reactions for both action and inaction (performing a behavior or not) across a range of health promoting and health risk behaviors are discussed, as well as implications for future intervention work.